2014
DOI: 10.1186/1476-072x-13-45
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural landscape and spatial distribution of Toxoplasma gondii in rural environment: an agent-based model

Abstract: BackgroundPredicting the spatial distribution of pathogens with an environmental stage is challenging because of the difficulty to detect them in environmental samples. Among these pathogens, the parasite Toxoplasma gondii is the causative agent of the zoonosis toxoplasmosis, which is responsible for public health issues. Oocysts of T. gondii are excreted by infected cats in the environment, where they may survive and remain infectious for intermediate hosts, specifically rodents, during months to years. The l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 44 publications
1
22
1
Order By: Relevance
“…The average annual seroconversion rates estimated on the five studied farms (0.42 for the farms B and T, 0.88 for the farm C and 0.96 for the farms A and F) are high compared to those previously reported in an urban population of stray cats (0.17 seroconversions/year) [ 35 ] and in three rural populations of owned domestic cats (0.26, 0.36 and 0.39 seroconversions/year) [ 36 ]. These results support previous findings showing that livestock farms are hotspots of T. gondii infection in rural areas [ 29 , 31 , 59 – 61 ]. However, the seroconversion rates, as well as the estimated seroprevalences were highly variable between farms (from 15.38 to 73.08% or from 29.63 to 73.08% depending on the selected cut-off value) and the range of seroprevalences we obtained corresponds to the range of seroprevalences in farm cats previously reported in the literature: 33.3% in Spain [ 62 ]; 41.9% [ 63 ]; 68% [ 64 ] and 53.19% [ 65 ] in the USA; 62% in the UK [ 66 ]; and 75% in Poland [ 67 ].…”
Section: Discussionsupporting
confidence: 92%
“…The average annual seroconversion rates estimated on the five studied farms (0.42 for the farms B and T, 0.88 for the farm C and 0.96 for the farms A and F) are high compared to those previously reported in an urban population of stray cats (0.17 seroconversions/year) [ 35 ] and in three rural populations of owned domestic cats (0.26, 0.36 and 0.39 seroconversions/year) [ 36 ]. These results support previous findings showing that livestock farms are hotspots of T. gondii infection in rural areas [ 29 , 31 , 59 – 61 ]. However, the seroconversion rates, as well as the estimated seroprevalences were highly variable between farms (from 15.38 to 73.08% or from 29.63 to 73.08% depending on the selected cut-off value) and the range of seroprevalences we obtained corresponds to the range of seroprevalences in farm cats previously reported in the literature: 33.3% in Spain [ 62 ]; 41.9% [ 63 ]; 68% [ 64 ] and 53.19% [ 65 ] in the USA; 62% in the UK [ 66 ]; and 75% in Poland [ 67 ].…”
Section: Discussionsupporting
confidence: 92%
“…Gotteland et al . developed an Agent Based Model (ABM) taking spatial distribution of landscape structures (farm buildings) into account [ 70 , 71 ]. They found that spatial distribution of farm buildings in rural environments is associated with the infection of humans and animals: humans and animals in the villages where the farms are located might be at a higher risk of exposure to T. gondii oocyst due to the high density of cats [ 70 , 71 ].…”
Section: Environmental Factors Influence the Occurrence Transmissionmentioning
confidence: 99%
“…In Agricultural landscape and spatial distribution of Toxoplasma gondii in rural environment: an agent-based model [ 23 ], the authors consider space essentially as a medium of interactions aiming, via multi-agent model, to predict the spatial distribution of a pathogenic factor (difficult to assess in real life), via a number of variables that seem to influence its distribution. Here the parasite is Toxoplasma gondii , which is responsible for toxoplasmosis and is excreted in the environment by infected cats (the definitive host) and rodents (intermediate host).…”
Section: Resultsmentioning
confidence: 99%